Peningkatan Kemampuan Menulis Resensi Novel dengan Menggunakan Metode Peta Pikiran pada Siswa Kelas XI SMA IT Izzuddin Palembang - Nugraha, A. Kahfi; Lestari, Hikmah; Fitriani, Yessi; Lestari, Rizcha Fuji (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to improve the learning outcomes of novel review writing for students of class XI MIPA 1 at SMA IT Izzuddin Palembang through the use of mind mapping learning methods. This research is a Classroom Action Research (CAR) conducted in two cycles. The results showed an increase in students' ability to write novel reviews after applying the mind mapping learning method. In the first cycle, the average score of students was 80 with a classical completeness percentage of 53%. In the second cycle, the average score of students increased to 87 with a classical completeness percentage of 94%. The obstacles faced in the first cycle, such as students' difficulties in developing themes and keywords using mind maps, as well as converting the results of mind maps into coherent narratives, could be minimized in the second cycle through improvements to the lesson plan. Overall, the use of mind mapping learning methods can improve the ability to write novel reviews for students of class XI MIPA 1 at SMA IT Izzuddin Palembang. This method is able to assist students in developing their ideas, thoughts, and thoughts in a structured manner so that they can be expressed in the form of well-organized and systematic novel review writings.